4D Golden‐Angle Radial MRI at Subsecond Temporal Resolution. (25th November 2022) - Feng, Li
Abstract: Intraframe motion blurring, as a major challenge in free‐breathing dynamic MRI, can be reduced if high temporal resolution can be achieved. To address this challenge, this work proposes a highly accelerated 4D (3D + time) dynamic MRI framework with subsecond temporal resolution that does not require explicit motion compensation. The method combines standard stack‐of‐stars golden‐angle radial sampling and tailored GRASP‐Pro (Golden‐angle RAdial Sparse Parallel imaging with imProved performance) reconstruction. Specifically, 4D dynamic MRI acquisition is performed continuously without motion gating or sorting. The k‐space centers in stack‐of‐stars radial data are organized to guide estimation of a temporal basis, with which GRASP‐Pro reconstruction is employed to enforce joint low‐rank subspace and sparsity constraints. This new basis estimation strategy is the new feature proposed for subspace‐based reconstruction in this work to achieve high temporal resolution (e.g., subsecond/3D volume). It does not require sequence modification to acquire additional navigation data, it is compatible with commercially available stack‐of‐stars sequences, and it does not need an intermediate reconstruction step. The proposed 4D dynamic MRI approach was tested in abdominal motion phantom, free‐breathing abdominal MRI, and dynamic contrast‐enhanced MRI (DCE‐MRI). Our results have shown that GRASP‐Pro reconstruction with the new basis estimation strategy enables highly‐accelerated 4D dynamic imaging at subsecond temporal resolution (with five spokes or less for each dynamic frame per image slice) for both free‐breathing non‐DCE‐MRI and DCE‐MRI. In the abdominal phantom, better image quality with lower root mean square error and higher structural similarity index was achieved using GRASP‐Pro compared with standard GRASP. With the ability to acquire each 3D image in less than 1 s, intraframe respiratory blurring can be intrinsically reduced for body applications with our approach, which eliminates the need for explicit motion detection and motion compensation. Abstract : This work proposes a highly‐accelerated 4D (3D + time) dynamic MRI framework with subsecond temporal resolution combining standard stack‐of‐stars golden‐angle radial sampling and tailored GRASP‐Pro (Golden‐angle RAdial Sparse Parallel imaging with imProved performance) reconstruction. Image reconstruction is performed using a combination of low‐rank subspace and sparsity constraints, where a temporal basis is estimated from the stack‐of‐stars k‐space centers to guide image reconstruction.